Swarms of Unmanned Aerial Vehicles – A Survey - Tahir Anam; Böling Jari; Haghbayan Mohammad-Hashem; Toivonen Hannu; Plosila Juha (Elsevier BV, 2022)
The purpose of this study is to focus on the analysis of the core characteristics of swarms of drones or Unmanned Aerial Vehicles and to present them in a way that facilitates analysis of public awareness on such swarms. Furthermore, the functionality, problems, and importance of drones are highlighted. Lastly, the experimental survey from a bunch of academic population demonstrates that the swarms of drones are fundamental future agendas and will be adapted by the time.